Mundo y trascendencia: apuntes sobre la dimensión ontológica del juego en Carlos Astrada y Eugen Fink - Mauna, Florencia (2023)
Inside the academy, game studies are usually marginalized by Scholars, underestimated as secondary issues to thought, or as spaces for discussion related to contemplative leisure. However, in opposition to this type of inference, we will dedicate ourselves entirely to vindicating the role of the game as a fundamental existential phenomenon in the question of being and its relationship with the world. In his paper, we will propose a playful and metaphysical intersection between two renowned thinkers: Carlos Astrada, an Argentine philosopher, and Eugen Fink, a German philosopher. Both authors share the Heideggerian heritage that they will discuss and that will serve as the guiding thread of the theoretical dialogue on the ontological nature of the game.